UPAYA MENINGKATKAN HASIL BELAJAR PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DENGAN MENGGUNAKAN PENDEKATAN RME SISWA SMK - Kurnia, Nia; Sari, Indah Puspita; Sugandi, Asep Ikin; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to analyze the improvement of learning outcomes on the material of a two-linear equation system using the Realistic Mathematics Education (RME) approach in class X SMK X Multimedia 3 Group B SMK TI Garuda Nusantara Cimahi. The research method used is a two-cycle class action research method. The subjects in this study were 13 students of class X SMK X Multimedia 3 Group B SMK TI Garuda Nusantara Cimahi. The instruments used are in the form of observation, documentation and test questions. The stages in this research are conducting a pre-cycle (before the action), doing work on the LKS, and finally doing a final test (after giving the action). The data processing technique used is using excel The results of this study indicate that the Realistic Mathematics Education (RME) approach can improve student learning outcomes at SMK TI Garuda Nusantara Cimahi class X Multimedia 3 Group B Multimedia.